Laparoscopic Appendectomy in Pregnancy: a Case Series of Seven Patients - Palanivelu, Chinnusamy (Society of Laparoendoscopic Surgeons, 2006)
BACKGROUND: Appendicitis in the pregnant patient presents with diagnostic difficulties and more serious problems. Open surgery has its own limitations, mostly governed by the stage of the disease and the trimester of pregnancy. Laparoscopic appendectomy is beginning to be recognized as standard appendicitis treatment, as evidenced by several studies. In pregnancy, laparoscopy is even more controversial. Several studies prove the safety of laparoscopy and some studies disprove it. METHODS: We have treated 7 patients in the last 10 years; 6 had acute appendicitis and 1 had a perforated appendix. Ultrasound diagnosed 5 patients, and CT scan identified the other 2 patients. The patient with the perforated appendix had free fluid in the right iliac fossa and pelvis. Laparoscopic appendectomy was done in all patients. DISCUSSION: Pregnancy poses its own unique problems to the surgeon and anesthesiologist. The normal physiology becomes altered, and sound knowledge of this is necessary to handle these patients. Clinical presentation was mostly straightforward. Both ultrasound and CT scan were useful investigations. CONCLUSION: Most studies support the use of laparoscopy in the management of appendicitis. There was no mortality (for mother and fetus) or morbidity in our patients.